So much to be done : the writings of breast cancer activist Barbara Brenner - Brenner, Barbara A. (University of Minnesota Press, 2016)
"What kind of cancer is it?" was the first question Barbara Brenner asked her doctor after hearing that the lump in her breast was malignant. His answer: "You don't need to know that." Wrong response. Brenner, who was already an activist, made knowing her business and spreading knowledge her mission. The power behind Breast Cancer Action® and its transformative Think Before You Pink campaign, Barbara Brenner brought an abundance of wit, courage, and clarity to the cause and forever changed the conversation. What had been construed as an individual crisis could now be seen for what it was: a pressing concern of public health and social justice, with environmental issues at the center of prevention efforts. Collected in So Much to Be Done, and framed by personal accounts of Barbara and her influential work, Brenner's columns and blog posts form a chronicle of breast cancer research and health care activism that is as inspiring as it is informative. As she takes on the corporate forces at work in breast cancer research and treatment and in the "pinkwashing" of fund-raising for the cause, Brenner, a self-described hell-raiser, contends with cancer herself, twice, and her words offer understanding and encouragement to all those whose lives are touched by the disease. When Brenner was diagnosed with ALS in 2011, she broadened her critique of health care while also writing about her own experience. Infused with her characteristic moxie, humor, anger, and compassion, these reflections from her last two years provide an in-depth, precisely observed portrayal of what it is to live with a terminal disease and to die on one's own terms